Shaken culture fermentation for production of microbial cellulose from pineapple waste - Norhayati Pa'e, 1983-, author; Ida Idayu Muhamad, author; International Conference & Exhibition on on Waste to Wealth (2007 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL